Listeria monocytogenes Invasion Into Sheep Kidney Epithelial Cells Depends on InlB, and Invasion Efficiency Is Modulated by Phylogenetically Defined InlB Isoforms - Chalenko, Yaroslava; Kolbasova, Olga; Pivova, Elena; Abdulkadieva, Mariam; Povolyaeva, Olga; Kalinin, Egor; Kolbasov, Denis; Ermolaeva, Svetlana (Frontiers in Microbiology, 2022)
The facultative intracellular pathogen L. monocytogenes is of major veterinary importance in small ruminants. Nevertheless, details of L. monocytogenes interactions with cells of small ruminants are not fully established. To study the potential of L. monocytogenes to infect sheep cells, we used the finite sheep kidney cell line (shKEC), which was infected with the wild-type L. monocytogenes strain EGDe. The invasion efficiency was 0.015 ± 0.004%. The invasion factor InlB was critically important for invasion, and inlB gene deletion almost prevented L. monocytogenes invasion into shKEC cells. Comparison of the potential of phylogenetically defined InlB isoforms to restore the invasive phenotype of the EGDeΔinlB strain demonstrated that although all InlB isoforms restored invasion of the EGDeΔinlB strain into shKEC cells, the InlB isoforms typical of highly virulent ruminant strains of the clonal complexes CC1 and CC7 were more efficient than isoforms typical of CC2 and CC9 strains (which are less virulent toward ruminants) in supporting invasion. L.monocytogenes effectively multiplied with a doubling of time in about 90 minutes after they entered the sheep cells. Intracellular bacteria moved using the well-known actin polymerization mechanism. Cell-to-cell spreading was restricted to the infection of a few tens of neighboring cells for 7 days. Overall, the obtained results demonstrated that (i) InlB is required for invasion into sheep cells, (ii) InlB isoforms might be important for hypervirulence of certain clonal groups toward ruminants, and (iii) L. monocytogenes effectively multiplies in ovine cells once entered.